Pasando el sombrero: una revisión del double-hatting desde la experiencia internacional y su influencia en la concentración de funciones dentro del circuito arbitral peruano - Schiappa-Pietra Fuentes, Giorgio (2023)
The Double-hatting in the "open exercise of the arbitration function" is understood as the premise of a reflection of the freedom of appointment and the same freedom of acceptance of the assignment to arbitrate that has had a great influence internationally and has been spreading around the world. In this sense, this article will provide a perspective on the influence it has had on the concentration of functions in the Peruvian arbitration circuit.